The Income Tax and Charitable Contributions - Feldstein, Martin; Taylor, Amy (Econometrica, 1976)
Charitable contributions are an important source of basic finance for a wide variety of private nonprofit organizations that perform quasi-public functions. The tax treatment of charitable contributions substantially influences the volume and distribution of these gifts. The current study presents new estimates of the price and income elasticities of charitable giving. The parameter estimates are then used with the United States Treasury Tax File to simulate the effects of several possible alternatives to the current tax treatment of charitable giving. INDIVIDUAL CHARITABLE CONTRIBUTIONS are an important source of basic finance for a wide variety of private nonprofit organizations. Higher education, research, health care, the visual and performing arts, welfare services, and community and religious activities rely heavily on the voluntary institution. In 1970, American families contributed more than $17 billion for their support. The volume and distribution of charitable gifts is influenced by the personal income tax treatment of charitable contributions. There are today a number of widely discussed proposals for changing these rules. The appropriate tax treatment of such gifts involves a complex series of economic issues. Critical to a resolution of these issues is an understanding of the likely quantitative effects of alternative tax rules: the effects on the total volume of charitable gifts and its distribution among the different types of donees; the effects on the distribution of tax burdens